Analysis of Consumer Legal Protection for Internet Services Indihome Rantauprapat Judging from Law Number 8 of 1999 concerning Consumer Protection - Muhammad Fauzan Hasibuan; Muhammad Yusuf Siregar; Wahyu Simon Tampubolon; Risdalina Risdalina (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
PT. Telkom is an industry that is engaged in telecommunications. One of the services offered by this industry is the provision of indihome internet services, television, landlines, cctv. In this case, PT. Telkom is the subject studied in this paper. This legal writing aims to find out the legal protection for consumers of IndiHome products. The cases discussed in the preparation of this law are related to the legal protection of consumers in subscribing to a product by PT. Telkom and the accountability efforts that PT. Telkom can provide to customers caused by the constraints of the services provided and the subscription contract agreement between PT. Telkom with customers which contains the rights and obligations of service providers and consumers that are binding on each other. The method used in this paper is using the Juridical Normative Empirical method. The results of the study indicate that consumer protection is regulated in Law No. 8 of 1999 concerning Consumer Protection which includes the rights and obligations of consumers or business actors.